Pengaruh Kreativitas Mengajar Guru Terhadap Hasil Belajar Siswa - Septy Yeremia S; Anisa Siregar; Rianta Malau; Rohyana Salmi R (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research aims to explore the impact of creativity in teaching methods on student learning outcomes. In this research, a qualitative approach with literature analysis is used as a method. The data taken comes from scientific studies relevant to the topic. Research findings show that teacher creativity in the teaching process has a significant influence on student achievement in learning. The mismatch of teaching media with the material being taught causes a lack of creativity in teaching, which in turn results in student boredom and lack of interest in lessons. As a result, student achievement levels tend to be low. On the other hand, a creative teaching approach is able to create an interesting learning environment, increase student motivation, and support their understanding of the subject matter. Apart from that, teacher creativity can also stimulate students to think critically, creatively and innovatively. Therefore, it is important for teachers to continue to develop creativity in their teaching methods in order to improve student learning outcomes.